Uncertainty Handling in medical diagnosis using probabilistic ML - Bushra, Haleema; Sharma, Manisha; Onapakala, Kiran; Rao Gumma, Yalamandeswara; Lata Gajpal, Anju (Journal of Neonatal Surgery, 2025)
In medical diagnosis, there is usually noisy, incomplete, or imprecise data that causes uncertainty in the decisions that are made. Powerful models Traditional machine learning models can be very powerful, but they tend to give deterministic predictions without considering the associated uncertainty. The given paper dwells upon the use of probabilistic machine learning (ML) methods to handle uncertainty in medical diagnostics. Probabilistic ML has advantages over modeling predictions as point estimates by providing interpretable measures of confidence to improve clinical trust, make risk-sensitive decisions, and improve the overall diagnostic accuracy. This work contains a comparative review of probabilistic techniques, such as Bayesian Neural Networks, Gaussian Processes, and Monte Carlo Dropout, on open health care data. The experiment results demonstrate that the inclusion of uncertainty estimation can already lead to a significant increase in performance and reliability which opens the door to safer AI-based medical systems.